Influência do solvente na obtenção de novos polímeros de coordenação baseados no ácido 2,5-piperazinadiona-1,4-diácetico e íons térbio trivalentes - Cunha, Luana Reine Pinheiro Lima (2020)
Coordination polymers (CP’s) are coordination compounds that repeat and extend in one, two or three dimensions. CP’s that extend in three dimensions, generating porous materials, are so called MOF’s (Metal Organic Frameworks). It is well established that MOF crystallization, structure and morphology are dependent of the metal center, ligand and several synthetic parameters, e. g. the choice of the solvent. Regarding this context, this work aimed to synthesize new Tb3+ coordination polymers using 2,5- piperazinedione-1,4-diacetic acid (DKP) and oxalic acid (Ox) as ligands and applying solvo / hydrothermal route with different solvents: water, N,N-dimethylformamide, ethanol and methanol yielding the CP’s designated as Tb-(DKP)(Ox)-A, Tb-(DKP)(Ox)- D, Tb-(DKP)(Ox)-E and Tb-(DKP)(Ox)-M, respectively. Synthesized compounds were characterized by dynamic light scattering (DLS), powder X-ray diffraction (DRX), infrared absorption spectroscopy (IR), thermogravimetric analysis (TGA) and luminescence spectroscopy. DRX results suggested that all synthesized CP’s are unpublished, once that they show different crystallographic patterns from those that can be found in the literature, was also verified that every synthesis yields a different structure as a function of the solvent, even that these structures were different, they presents higher compatibility when compared to others. Infrared absorption spectra indicates that ligand structure were preserved while the coordination net was formed, being observed the displacement of the functional groups vibrational frequency as a result of the coordination to the metal center. Themogravimetric data was helpful to assign chemical formulas to the synthesized Tb-(DKP)(Ox)-A, Tb-(DKP)(Ox)-D, Tb-(DKP)(Ox)-E and Tb- (DKP)(Ox)-M, respectively, as: {[Tb2(DKP)(Ox)2(H2O)3,5](H2O)]}, {[Tb2(DKP)2,5(Ox)0,5(H2O)3](H2O)3(DMF)2]}, [Tb2(DKP)1,5(Ox)1,5(H2O)7] and [Tb2(DKP)1,5(Ox)1,5(H2O)3], these assignments were also based on similar formulas proposed on the literature. Comparing the mass loss (TGA percentual) and the temperature ranges for removal of coordinated and non-coordinate solvent molecules and also the total decomposition of DKP and Ox ligands of the synthesized compounds, Tb- (DKP)(Ox)-E is the most thermal stable. From themogravimetric results, considering the chemical composition for the CP's synthesized on each solvent, water, N,N- dimethylformamide, ethanol and methanol synthetic yielding were 47,6%, 61%, 70% and 84%, respectively. The excitation and emission spectra of Tb-(DKP)(Ox)-E, Tb- (DKP)(Ox)-M e Tb-(DKP)(Ox)-D and Tb-(DKP)(Ox)-A are quite similar. A broad band with low intensity observed around 250-300 nm was attributed to the indirect excitation of the Tb3+ ion through intraligand S0 → S1 transition centered at the DKP. Intraconfigurational-4f8 transitions appears as sharp bands on the excitation spectra, as a result of direct excitation from the ground state, 7F6, to one of the excited levels of the Tb3+ ion. Emission spectra of the synthesized compounds exhibits a highly intense band around 545 nm, characteristic of the 5D4 → 7F5 transition. DLS characterization indicated that all compounds but Tb-(DKP)(Ox)-M, have similar polydispersity. From DLS data was observed that synthesized compounds lies between 0-1, what made possible to infer that all samples were monodisperse and stable. It was also noted that Tb-(DKP)(Ox)-E presented the smallest hydrodynamic diameter, with a population of 478.26 nm when compared to the other synthesized compounds. The results from all characterizations performed on the compounds allowed us to observe the influence of the studied solvents on the properties of the compounds obtained. Also, the studies developed in this dissertation can be used as a ground to the future development of this research, one possibility is the investigation of possible applications of the synthesized Tb3+ compounds as catalysts on organic reactions.